A business process improvement framework to facilitate superior SME operations. (5th February 2008) - Khan, Zulfiqar; Bali, Rajeev K.; Wickramasinghe, Nilmini
The present climate that UK companies face is quite volatile. Organisations are now focusing on their core competencies (doing what they are best at) and outsourcing most other activities. Administration functions of some service organisations are also being outsourced to specialists here in the UK and abroad. In order that UK organisations achieve world class levels of competitiveness the DTI's UK Manufacturing Strategy identified an urgent need for the systematic implementation of 'best practices' such as lean practices and other World Class Manufacturing (WCM) methodologies. The paper uses a case study methodology to test and analyse a Small and Medium Enterprise (SME) specific framework. This case study is used to test and validate the Business Process Improvement (BPI) framework.